Legal Status of the Who’s Covid-19 Investigator in International Law Perspective - Suryokumoro, Herman; Ula, Hikmatul; R, Intania Zahra (SASI, 2022)
Introduction: This issue was raised based on the fact that the COVID-19 investigation team in carrying out their duties did not always go well, one of which was the refusal of several people from the investigation team to enter Chinese territory.Purposes of the Research: This study aims to analyze the legal protection of the COVID-19 investigator team from WHO in the perspective of international law.Methods of the Research: The research method used is normative juridical research with a qualitative analytical descriptive nature, by examining legal materials, both primary legal materials and secondary legal materials through literature studies and other related literature.Results of the Research: The position of the WHO investigation team in the perspective of international law is as an expert on mission as well as an expert on mission in the United Nations. Expert on mission is an external organ to assist the functions and goals of organizations including WHO. In carrying out their duties, the expert on mission is equipped with all legal protections as stipulated in the Convention on the Privileges and Immunities of the Specialized Agencies. Protection is given when the expert mission is carrying out its duties but in the convention there is no guarantee that the expert on mission is allowed -unconditionally- to enter the territory of the country. This is very reasonable considering that the state has full sovereignty over its jurisdiction. The ban on the entry of the COVID-19 investigation team for reasons of sovereignty should have been avoided considering that the COVID-19 pandemic is a common problem that requires cooperation from all over the world. The existence of obstacles to the work of the Investigation Team by China, which incidentally is the country that initiated the formation of the Covid-19 Investigation Team, is a bad precedent and a violation of international obligations as stipulated in the Responsibility of States for International Wrongful Acts.